2020
DOI: 10.1088/1748-9326/ab6789
|View full text |Cite
|
Sign up to set email alerts
|

Power, proximity, and physiology: does income inequality and racial composition amplify the impacts of air pollution on life expectancy in the United States?

Abstract: This study advances research at the intersection of environmental degradation, social stratification, and population health in the United States. Expanding the theoretical principles of power, proximity, and physiology, we hypothesize that the harmful effect of fine particulate matter on life expectancy is greater in states with higher levels of income inequality and larger black populations. To test our hypothesis, we use two-way fixed effects regression analysis to estimate the effect of a three-way interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…We conclude by reiterating that drug-related mortality is likely a deleterious "downstream" consequence of changes in the U.S. economy over the past half-century that have led to increased income inequality and an exploitive private health care and pharmaceutical industry. Our emphasis on the role of income inequality in the current drug overdose epidemic is consistent with recent research demonstrating that growing income inequality is a key determinant of other health-related outcomes, including overall life expectancy, crime, and mental illness as well as anthropogenic greenhouse gas emissions that cause climate change and exacerbate air pollution's impact on public health (Hill, Jorgenson et al 2019;Hill and Jorgenson 2018;Jorgenson et al 2016Jorgenson et al , 2017Jorgenson et al , 2020Knight, Schor, and Jorgenson 2017;Pickett and Wilkinson 2015). Therefore, addressing the supply side of the drug overdose epidemic is certainly warranted, but taking a more structural perspective to the epidemic that involves reducing income inequality would likely not only lead to reduced drug-related mortality but also have positive economic and environmental benefits.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We conclude by reiterating that drug-related mortality is likely a deleterious "downstream" consequence of changes in the U.S. economy over the past half-century that have led to increased income inequality and an exploitive private health care and pharmaceutical industry. Our emphasis on the role of income inequality in the current drug overdose epidemic is consistent with recent research demonstrating that growing income inequality is a key determinant of other health-related outcomes, including overall life expectancy, crime, and mental illness as well as anthropogenic greenhouse gas emissions that cause climate change and exacerbate air pollution's impact on public health (Hill, Jorgenson et al 2019;Hill and Jorgenson 2018;Jorgenson et al 2016Jorgenson et al , 2017Jorgenson et al , 2020Knight, Schor, and Jorgenson 2017;Pickett and Wilkinson 2015). Therefore, addressing the supply side of the drug overdose epidemic is certainly warranted, but taking a more structural perspective to the epidemic that involves reducing income inequality would likely not only lead to reduced drug-related mortality but also have positive economic and environmental benefits.…”
Section: Discussionsupporting
confidence: 84%
“…A large body of research in the social sciences suggests that inequality is a key driver of a range of health-related outcomes (see Pickett and Wilkinson 2015; Wilkinson and Pickett 2010, 2019). Recent studies that used relatively more sophisticated statistical modeling techniques have provided empirical evidence of the detrimental health impacts of macro levels of income inequality, especially reductions in country-level and U.S. state-level average life expectancy (e.g., Curran and Mahutga 2018; Hill and Jorgenson 2018; Jorgenson et al 2020). A number of studies have also observed inequality to be associated with adult and infant mortality, obesity, HIV infections, mental illness, and homicides (Buot et al 2014; Daly 2016; Ribeiro et al 2017; Torre and Myrskylä 2014; Wilkinson and Pickett 2010, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few studies have examined differential susceptibility by income inequality, mounting evidence suggests higher inequality magnifies the negative effects of AP on life expectancy ( Hill et al. 2019 ; Jorgenson et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that being part of the richest 20% is associated with a better biomarker profile is a confirmation of the many pathways through which having more resources can result in better health outcomes. Importantly, our analysis adds to the growing evidence that income inequality undermines population health, either on its own or as an effect modifier that worsens the effects of established determinantal factors to the health of populations ( Babones, 2008 ; Backlund et al, 2007 ; Hill et al, 2019 ; Jorgenson et al, 2020 ; Kaplan et al, 1996 ; Thombs et al, 2020 ). For example, a recent analysis by Hill and Jorgenson found that state-level income inequality undermines the life expectancy of both women and men in the Unites States ( Hill & Jorgenson, 2018 ).…”
Section: Discussionmentioning
confidence: 90%